IDENTIFICATION OF GEOMORPHOLOGY AND LITOLOGY BASED ON ANALYSIS OF LANDSAT-8 SATELLITE IMAGES IN PADANG CITY - Dewi Ramadhan; Srikandi Putri (Remote Sensing Technology Study Program, 2020)
The application of remote sensing to obtain better quality and up to date maps is needs to be done through the utilization of lithology and geomorphology in mapping of Padang city. This study aims to obtain a lithological and geomorphological picture of the appearance of Landsat-8 OLI Composite 567 satellite imagery. The research method was carried out by image interpretation data preparation. The results showed the city of Padang has 2 units of landforms from visual interpretation, namely fluvial and denudational landforms. Lithology identification in Padang using geological imagery and maps as a reference succeeds to acquire geological and lithological units, namely: Alluvial Fan which is smooth texture, lowland topography, hue and color is bright, parallel river flow patterns, sparse vegetation, river area associations. Non-decomposed flow texture is rather rough, hilly topography, hue and color is dark, radial river flow patterns, dense vegetation, associated with forests. Andesite has a rather rough texture, highland topography, hue and color is dark, radial river flow patterns, dense vegetation, associated with mountainous terrain. Alluvial is found in coastal areas, lakes and sandy areas, fine texture, lowland topography, alongside large rivers with valley, has a bright color and hue, its flow patterns are parallel, sparse vegetation, river area associations. Hardened Crystal Tuff with a rather rough texture, topography in mountainous areas, hues and color is dark, radial river flow patterns, dense vegetation, hill area associations. Volcanic Rock has a rough texture, high terrain topography, has dark colors and hues, radial river flow patterns, has dense vegetation, and is associated with mountains.